(untitled) (Farabi Journal of Social Sciences, 2020)
The article reveals the knowledge of a foreign language that implies not only the ability to speak or write in a foreign language but conducting intercultural dialogue, which requires not only language, but also cultural, country studies and other training. Readiness for film intercultural communication is the key to success both in the professional sphere and in the sphere of personal self-realization.Also it was focused on the most effective method of work will be a conversation about whether the expectations associated with the title of the film and the illustration on the cover were met. The use of authentic feature films in the process of teaching a foreign language has become firmly established in the practice of modern school and University teaching. but also more broadly - to conduct intercultural dialogue, which requires not only language, but also cultural, country studies and other training. The analysis of methodical literature confirms the expediency of using authentic feature films in the process of teaching a foreign language.